Laryngeal Adenoid Cystic Carcinoma: A rare neoplasm with still undefined treatment aspects. Case report and literature review - Gianluigi Mariano Grilli; Rossana Giancaspro; Valeria Fiore; Anna Del Colle; Luciano Enrico Renato Magaldi; Giuseppe Pannone (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2020)
Adenoid Cystic Carcinoma (ACC) is a rare malignant tumor, accounting for about 1% of head and neck malignancies and 10% of salivary gland cancers. The laryngeal localization of ACC is particularly rare because of the paucity of accessory salivary glands in this anatomical district. Prevalence is highest in the fifth and sixth decade of life with a slight female predilection and aetiology is unknown. Since laryngeal ACC characteristically grows slowly and occurs in the subglottis, the diagnosis, which is based on the combination of physical examination with fiberoscopy and neck-chest Computerized Tomography (CT), is often delayed. Nowadays the debate is still open about which is the best comprehensive therapy of this tumor. We present the case of a laryngeal ACC in a 68 year-old-woman, treated with total laryngectomy together with bilateral neck dissection and a literature review made with the purpose to point out the most recent advancements towards the definition of a gold-standard therapy. Laryngectomy results as the first choice treatment, while chemotherapy has minimal effects on this neoplasm and radiotherapy alone does not show the capacity to lead to complete resolution, but there is still the need of further studies to clarify the usefulness and the role played by neck dissection and postoperative radiotherapy.